Preparation method and application of NiFe-BTC-based MOF material

By preparing the Nife-BTC base MOF material, the existing non-valuable metal catalyst responded to the problem of slow dynamics, poor stability, and sensitivity to acidic environment in electro-catalytic oxygen reactions, and realized the high efficiency and stability of the electrolyte hydrogen hydrogen hydrogen. Electric catalytic performance.

CN119350643APending Publication Date: 2025-01-24CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477044.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing non-precious metal catalysts have problems such as slow reaction kinetics, poor stability and sensitivity to the acidic environment in electrocatalytic oxygen evolution reactions, which limits their application in electrolytic hydrogen production.

Method used

The NIFE-BTC base MOF material is used as electrocatalysts. By reacting the nickel nickel acetate and sulfuricate of tetrawater acetate at specific conditions, the NIFE-BTC base MOF with excellent electrical catalytic activity and stability is prepared Material.

Benefits of technology

NIFE-BTC-based MOF materials show excellent electrocatalyst activity and stability in the electro-catalytic oxygen reaction, which can effectively deal with the effects of the acidic environment and improve the overall efficiency of electrolytic water hydrogen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350643A_ABST
    Figure CN119350643A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a NiFe-BTC-based MOF material, and belongs to the technical field of electrocatalysts.The preparation method comprises the steps that nickel acetate tetrahydrate and ferrous sulfate heptahydrate are added into a mixed solvent composed of DMF, absolute ethyl alcohol and deionized water, after complete dissolution, a nickel acetate and ferrous sulfate mixed solution is obtained, then trimesic acid is added into DMF to be dissolved, and after complete dissolution, the nickel acetate and ferrous sulfate mixed solution is obtained; then adding monocarboxylate, uniformly mixing, adding into a mixed solution of nickel acetate and ferrous sulfate, uniformly mixing, stirring and reacting at 120-180 DEG C, carrying out solid-liquid separation on a reaction product, and finally washing and drying to obtain the nickel-nickel-ferrous sulfate composite material. Compared with an existing method, the method is easy to operate and low in cost, and the prepared NiFe-BTC-based MOF material has excellent electrocatalytic activity and stability in an electrocatalytic oxygen evolution reaction and can serve as an electrocatalyst to be applied to the field of water electrolysis hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a NiFe-BTC-based MOF material, belonging to the technical field of electrocatalysts. Background Art

[0002] As the global energy crisis and environmental problems become increasingly serious, reducing carbon emissions and finding alternative clean energy have become urgent goals for scientists to solve and seek development. At present, industries such as wind energy, tidal energy, geothermal energy, and solar energy have achieved rapid development in renewable energy research. However, most of these renewable energy sources are limited by external factors such as weather and environment. In addition, the instability of energy supply, low conversion efficiency, and high cost also make it impossible for most new energy industries to achieve large-scale development and short-term efficient energy acquisition. In contrast, the hydrogen energy industry has become the focus of future industries.

[0003] Hydrogen energy usually uses hydrogen as an energy medium. The chemical energy released by the chemical reaction between hydrogen and oxygen is converted into energy forms such as heat and electricity for use. It is a new type of secondary energy and a clean energy that is being accelerated in the context of "carbon peak and carbon neutrality". The acquisition of hydrogen energy usually requires the preparation of other energy sources. Compared with other preparation methods, hydrogen production by water electrolysis is more economical and environmentally friendly. In the process of water electrolysis, water molecules in the electrolyte are decomposed into hydrogen ions and oxygen ions under the action of electrons, and then these ions move to the two electrodes respectively under the action of the electric field. The hydrogen ions at the cathode are reduced to hydrogen after gaining electrons, while the oxygen ions at the anode are oxidized to oxygen after losing electrons, corresponding to the two half reactions of hydrogen evolution (HER) and oxygen evolution (OER). Compared with HER, OER exhibits a more complex catalytic mechanism, and its catalytic performance directly determines the overall efficiency of hydrogen production by water electrolysis. Therefore, the development of efficient and stable OER electrocatalysts is of great significance to promote the development of water electrolysis hydrogen production technology.

[0004] Traditional noble metal-based catalyst materials show high activity in OER, but their scarcity and high cost limit their large-scale application. Therefore, finding alternative non-noble metal catalysts has become a research hotspot. The application of non-noble metals in electrocatalytic OER has received extensive attention and research in recent years. Common transition metal elements (Fe, Co, Ni, etc.) are low in price, abundant in reserves, and durable. Non-metallic elements (C, O, S, P, etc.) are highly abundant on the earth and easy to obtain. Metal-free materials (such as graphene, carbon nanotubes, etc.) not only have large specific surface areas, but also have stable chemical properties and high mechanical strength. They all have great application potential. Although non-noble metal catalysts have made some progress in electrocatalytic OER, there are still some challenges. For example, the acidic environment has a great influence on the electrolytic water splitting performance of non-noble metal catalysts, and catalysts with faster reaction kinetics need to be designed to meet this challenge. In addition, the stability and life of the catalyst are also issues that need to be considered in practical applications.

[0005] Metal-organic frameworks (MOFs) are a class of crystalline materials with high specific surface area, adjustable pore structure and diversified chemical functions, and are considered to be potential alternative catalysts. The metal nodes in MOFs can serve as catalytic active centers, providing a rich chemical environment to regulate electron transport and the surface properties of the catalyst. Many literature reports show good electrocatalytic performance such as low overpotential and small Tafel slope. This is mainly due to the rich electrocatalytic active sites of MOF materials, which are derived from their inherent porosity and hybrid properties. However, traditional MOFs materials always exist in the form of bulk materials, with a limited number of exposed active sites. Secondly, MOFs materials have low electrical conductivity, slow ion transport behavior and stability that needs to be improved. Summary of the invention

[0006] The purpose of the present invention is to solve the deficiencies of the prior art and provide a method for preparing a NiFe-BTC-based MOF material. The method is simple to operate and low in cost. The prepared NiFe-BTC-based MOF material has excellent electrocatalytic activity and stability in the electrocatalytic oxygen evolution reaction.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a NiFe-BTC-based MOF material comprises the following steps:

[0009] (1) adding nickel acetate tetrahydrate and ferrous sulfate heptahydrate into a mixed solvent consisting of DMF, anhydrous ethanol and deionized water, and dissolving them completely to obtain a mixed solution of nickel acetate and ferrous sulfate;

[0010] (2) adding trimesic acid (H3BTC) into DMF to dissolve, then adding monocarboxylate, mixing evenly, adding to the mixed solution of nickel acetate and ferrous sulfate obtained in step (1), mixing evenly, stirring and reacting at 120-180° C. to obtain a reaction product;

[0011] (3) The reaction product is separated into solid and liquid, and then washed and dried to obtain a NiFe-BTC-based MOF material.

[0012] Furthermore, in step (1), the molar ratio of the nickel acetate tetrahydrate to the ferrous sulfate heptahydrate is 2:1.

[0013] Furthermore, in step (1), in the mixed solvent, the volume ratio of DMF, anhydrous ethanol and deionized water is 1:2:2.

[0014] Furthermore, in step (2), the monocarboxylate is sodium acetate or ammonium benzoate.

[0015] Furthermore, in step (2), the molar ratio of trimesic acid to nickel acetate tetrahydrate is (0.5-1):1, and the molar ratio of the monocarboxylate to trimesic acid is (0.5-1):1.

[0016] Furthermore, in step (2), the reaction temperature is 150° C. and the reaction time is 6 hours.

[0017] Furthermore, in step (3), the drying temperature is 60° C. and the drying time is 12 h.

[0018] The NiFe-BTC-based MOF material was prepared using the above method.

[0019] The NiFe-BTC-based MOF material prepared by the above method is used as an electrocatalyst in hydrogen production by water electrolysis.

[0020] Beneficial effects of the present invention:

[0021] The present invention provides a method for preparing a NiFe-BTC-based MOF material, wherein nickel acetate tetrahydrate and ferrous sulfate heptahydrate are used as metal sources, trimesic acid is used as an organic ligand, and monocarboxylate is used as a regulating carboxylic acid ligand to synthesize the NiFe-BTC-based MOF material. The method is simple to operate and low in cost. The prepared NiFe-BTC-based MOF material has excellent electrocatalytic activity and stability in an electrocatalytic oxygen evolution reaction, and can be used as an electrocatalyst in the field of electrolysis of water for hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a transmission electron microscopy image of the MOF material prepared in Comparative Example 1-2;

[0023] Figure 2 Transmission electron microscopy image of the MOF material prepared in Example 1-2;

[0024] Figure 3 XRD diagrams of MOF materials prepared in Examples 1-2 and Comparative Examples 1-2;

[0025] Figure 4 The infrared spectra of the MOF materials prepared in Example 1-2 and Comparative Example 1-2;

[0026] Figure 5 This is the XPS spectrum of the MOF material prepared in Comparative Example 2;

[0027] Figure 6 This is the XPS spectrum of the MOF material prepared in Example 1;

[0028] Figure 7 LSV curves of electrodes prepared using the MOF materials of Examples 1-2 and Comparative Examples 1-2;

[0029] Figure 8 CV curves of electrodes prepared using the MOF materials of Examples 1-2 and Comparative Examples 1-2 in the potential range of 0096-1.096 V;

[0030] Fig. 9 A graph showing the relationship between the current density difference at 1.07 V and the non-Faraday scan rate of electrodes prepared using the MOF materials of Example 1-2 and Comparative Example 1-2;

[0031] Fig.10 The electrochemical impedance spectra of electrodes prepared using the MOF materials of Examples 1-2 and Comparative Examples 1-2 are shown. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings and specific embodiments.

[0033] Comparative Example 1

[0034] A method for preparing Ni-BTC based MOF material:

[0035] (1) adding 0.4 mmol of nickel acetate tetrahydrate into a mixed solvent consisting of 5 mL of DMF, 10 mL of anhydrous ethanol and 10 mL of deionized water, and dissolving the mixture completely to obtain an aqueous solution of nickel acetate;

[0036] (2) adding 0.4 mmol of trimesic acid into 5 mL of DMF to dissolve, and then adding the mixture into the nickel acetate and ferrous sulfate mixture obtained in step (1), mixing evenly, and stirring at 150° C. and 600 rpm for 6 h to obtain a reaction product;

[0037] (3) After the reaction product was centrifuged, the solid product was washed three times with deionized water and ethanol respectively, and finally dried in an oven at 60° C. for 12 h to obtain a Ni-BTC-based MOF material, which was recorded as Ni-BTC.

[0038] Comparative Example 2

[0039] A method for preparing a NiFe-BTC-based MOF material comprises the following steps:

[0040] (1) adding 0.4 mmol of nickel acetate tetrahydrate and 0.2 mmol of ferrous sulfate heptahydrate into a mixed solvent consisting of 5 mL of DMF, 10 mL of anhydrous ethanol and 10 mL of deionized water, and dissolving them completely to obtain a mixed solution of nickel acetate and ferrous sulfate;

[0041] (2) adding 0.4 mmol of trimesic acid into 5 mL of DMF to dissolve, and then adding the mixture into the nickel acetate and ferrous sulfate mixture obtained in step (1), mixing evenly, and stirring at 150° C. and 600 rpm for 6 h to obtain a reaction product;

[0042] (3) After the reaction product was centrifuged, the solid product was washed three times with deionized water and ethanol respectively, and finally dried in an oven at 60° C. for 12 h to obtain a NiFe-BTC-based MOF material, which was recorded as NiFe-BTC.

[0043] Example 1

[0044] A method for preparing a NiFe-BTC-based MOF material comprises the following steps:

[0045] (1) adding 0.4 mmol of nickel acetate tetrahydrate and 0.2 mmol of ferrous sulfate heptahydrate into a mixed solvent consisting of 5 mL of DMF, 10 mL of anhydrous ethanol and 10 mL of deionized water, and dissolving them completely to obtain a mixed solution of nickel acetate and ferrous sulfate;

[0046] (2) adding 0.4 mmol of trimesic acid and 0.3 mmol of sodium acetate into 5 mL of DMF to completely dissolve, and then adding the mixture into the nickel acetate and ferrous sulfate solution obtained in step (1), mixing evenly, and stirring at 150° C. and 600 rpm for 6 h to obtain a reaction product;

[0047] (3) After the reaction product was centrifuged, the solid product was washed three times with deionized water and ethanol respectively, and finally dried in an oven at 60° C. for 12 h to obtain a NiFe-BTC-based MOF material, which was recorded as NiFe-BTC-OAc.

[0048] Example 2

[0049] The sodium acetate in step (2) was replaced with ammonium benzoate, and the rest was the same as in Example 1. The obtained NiFe-BTC-based MOF material was denoted as NiFe-BTC-PhCOO.

[0050] Figure 1 This is a transmission electron microscopy image of the MOF material prepared in Comparative Example 1-2, wherein: Figure 1 (a) and Figure 1 (b) is a transmission electron microscopy image of Ni-BTC prepared in Comparative Example 1. Figure 1 (c) and Figure 1 (d) is a transmission electron microscope image of NiFe-BTC prepared in Comparative Example 2. It can be seen that the overall size of Ni-BTC and NiFe-BTC are relatively large, mainly showing the morphology of rigid sheets, with obvious superposition phenomenon. By comparison, it is found that the surface of Ni-BTC material is smooth, while the bimetallic NiFe-BTC material synthesized by introducing Fe presents a rough surface, and the surface of the sheet morphology has obvious hollowing phenomenon, forming many gaps of different sizes. It is speculated that this may be due to the introduction of Fe interfering with the coordination structure of the original Ni-BTC material and preventing the formation of surface coordination bonds. Through the analysis of a large number of literature, this rough and porous surface is conducive to the improvement of the catalytic activity of the electrocatalyst.

[0051] Figure 2 This is a transmission electron micrograph of the MOF material prepared in Example 1-2, wherein Figure 2 (a) and Figure 2 (b) is a transmission electron microscopy image of NiFe-BTC-OAc prepared in Example 1, Figure 2 (c) and Figure 2 (d) is a transmission electron microscope image of NiFe-BTC-PhCOO prepared in Example 2. It can be seen that compared with Ni-BTC and NiFe-BTC in Comparative Examples 1-2, NiFe-BTC-OAc no longer presents the morphology of a rigid sheet, and its morphology is relatively uniform, the size is significantly reduced, the diameter is between a dozen nanometers and tens of nanometers, and there is a certain degree of adhesion between them. In contrast, NiFe-BTC-PhCOO can still maintain part of the original sheet morphology, but the surface becomes rough, the thickness is significantly thinner, and a certain amount of irregular flaky products are generated around it. It shows that after the addition of monocarboxylates, the MOFs materials have undergone very obvious changes in morphology. Acetate realizes the transformation of NiFe-BTC from thick sheets to nanoparticles, while benzoate transforms NiFe-BTC from thick sheets to thin sheets, proving that monocarboxylic acids have a certain ability to regulate the morphology of MOFs materials.

[0052] Figure 3 The XRD diagrams of the MOF materials prepared in Examples 1-2 and Comparative Examples 1-2 are shown in FIG. Figure 3(a) is the XRD pattern of the MOF material prepared in Comparative Example 1-2, Figure 3 (b) is the XRD pattern of the MOF material prepared in Example 1-2. Figure 3 (a) It can be seen that Ni-BTC and NiFe-BTC have strong diffraction peaks at 2θ=12.34° and 18.48°, which is completely consistent with the standard spectrum (CCDC No.636900), proving that the two MOFs materials Ni-BTC and NiFe-BTC have been successfully synthesized. In addition, by comparing the XRD patterns of Ni-BTC and NiFe-BTC, we can find that the introduction of Fe does not change the overall structure of the MOFs material, and still maintains a good crystal configuration, in which Ni and Fe atoms exist in the same coordination mode in the bimetallic NiFe-BTC material. Figure 3 (b) It can be seen that compared with the standard Ni-BTC, the diffraction peak shape of NiFe-BTC-OAc is basically consistent, and very obvious characteristic peaks appear at 2θ=12.34° and 18.48°, indicating that the introduction of sodium acetate does not change the physical phase of NiFe-BTC, and NiFe-BTC-OAc still maintains the same structural characteristics as NiFe-BTC. However, NiFe-BTC-PhCOO shows a different peak shape, the strongest characteristic diffraction peak at 2θ=12.34° disappears, and the characteristic diffraction peak at 2θ=18.48° becomes significantly weaker, and some peaks are shifted, and a new peak appears (2θ=26.24°). The results show that the introduction of benzoate has a great influence on the structure of NiFe-BTC, causing the original NiFe-BTC structure to change.

[0053] Figure 4 The infrared spectra of the MOF materials prepared in Example 1-2 and Comparative Example 1-2 are shown in FIG. Figure 4 (a) is the infrared spectrum of the MOF material prepared in Comparative Example 1-2, Figure 4 (b) is the infrared spectrum of the MOF material prepared in Example 1-2, Figure 4 (a) It can be seen that compared with H3BTC, the -OH and H2O vibration peaks in Ni-BTC and NiFe-BTC materials are significantly shifted to the left, which may be caused by the hydrogen bonding between molecules in MOFs materials. -1 , and 1452cm -1 There are two obvious characteristic absorption peaks near the carboxylic acid group, which are respectively attributed to the OC=O and CH groups in the carboxylic acid group. After coordination with metal ions, the OC=O peak in Ni-BTC and NiFe-BTC materials splits into asymmetric and symmetric vibrations (~1602cm -1 and 1375cm -1 ); Combine Figure 4 (b) It can be seen that NiFe-BTC-OAc basically maintains the original characteristic absorption peak, while the peak intensity of NiFe-BTC-PhCOO is smaller than that of NiFe-BTC, and many characteristic absorption peaks disappear. In addition, compared with the benzoate raw material, the peak intensity of NiFe-BTC-PhCOO is 0.1777 W / cm2 at 800 cm -1 The absorption peak at is not obvious, and it is speculated that the crystal structure of NiFe-BTC-PhCOO has changed compared with NiFe-BTC. Therefore, infrared analysis further proves that different carboxylates have different regulatory effects on NiFe-BTC. Acetate has no effect on the overall structure of NiFe-BTC during the competitive coordination process due to its small molecule, while benzoic acid has a significant effect during the competitive coordination process due to its similar structure to trimesic acid, causing a significant change in its structure.

[0054] Figure 5 This is the XPS spectrum of the MOF material prepared in Comparative Example 2, where: Figure 5 (a) is the full spectrum, Figure 5 (b) is the Ni2p diagram, Figure 5 (c) is the O1s diagram, Figure 5 (d) is the Fe2p diagram; Figure 6 This is the XPS spectrum of the MOF material prepared in Example 1, wherein: Figure 6 (a) is the full spectrum, Figure 6 (b) is the Ni2p diagram, Figure 6 (c) is the O1s diagram, Figure 6 (d) is the Fe2p diagram. Figure 5 and Figure 6It can be seen that both NiFe-BTC and NiFe-BTC-OAc are composed of four elements: Ni, Fe, C and O. The peak of N element mainly comes from the influence of N element in environmental factors. Ni(II) and Fe(II) species can be clearly observed in the spectra of Ni 2p peak and Fe 2p peak, accompanied by high-valence Ni(III) and Fe(III) species. Compared with NiFe-BTC, NiFeBTC-OAc Ni 2p spectrum shows a high-energy shifted Ni 2p peak (0.1eV higher than NiFe-BTC-OAc), which is mainly due to the introduction of acetate radicals to change the local electronic structure of Ni atoms to a certain extent. Similarly, compared with NiFeBTC-OAc, the Fe 2p peak of NiFe-BTC moves to a higher binding energy (0.8eV), which is clearly illustrated in the Fe 2p XPS spectrum. The high-energy shifts of Ni 2p and Fe 2p peaks indicate that there is a strong electronic interaction between Ni and Fe in the bimetallic NiFe-MOF, and the subsequent synergistic effect can enhance the OER catalytic performance. More importantly, the introduction of nickel acetate increases the concentration of high-valent Ni(III) and Fe(III) in the MOFs material, which is conducive to the electrocatalytic oxygen evolution reaction.

[0055] The MOF materials prepared in Example 1-2 and Comparative Example 1-2 were prepared into electrodes, and then the electrocatalytic performance was tested. Test method: Accurately weigh 5 mg of the prepared MOF material and 5 mg of carbon powder, and put them together in a clean sample tube. Subsequently, 750 μL of anhydrous ethanol, 200 μL of deionized water and 50 μL of Nafion solution were added to the sample tube in sequence using a pipette. The sample tube containing the mixture was placed in an ultrasonic cleaner and subjected to ultrasonic treatment for 1 hour to ensure that all components were completely dispersed and evenly mixed to form a stable catalyst ink slurry. Subsequently, 10 μL of ink was dropped onto the polished GC disk electrode to ensure that the ink slurry formed a uniform thin film on the electrode surface. The electrode coated with the catalyst ink slurry was placed in a suitable environment and allowed to dry naturally to form a stable dry electrode coating. The dried electrode coating will be used as a working electrode for subsequent electrochemical oxygen reduction reaction (OER) performance testing. The OER performance test of the catalyst was carried out using a standard three-electrode system, and the equipment used was the Shanghai Chenhua CHI760e electrochemical workstation. The working electrode is a glassy carbon electrode loaded with the prepared MOFs catalyst material coating. The reference electrode is a mercury oxide electrode (Hg / HgO). The counter electrode uses a metal platinum wire as an auxiliary electrode. The electrolyte used in the experiment is a 1.0 mol / L KOH aqueous solution prepared in the laboratory. The working electrode is connected to the electrochemical workstation and the current is 5 mV s -1Linear sweep voltammetry was recorded at a scan rate of 100 0.0 ... RHE =E Hg / HgO +0.098+0.0592×pH. Overpotential (η) according to the formula η=E RHE -1.23V calculated.

[0056] Figure 7 is the LSV curve of the electrode prepared by using the MOF materials of Examples 1-2 and Comparative Examples 1-2, wherein Figure 7 (a) is the LSV curve, Figure 7 (b) is the overpotential test result, Figure 7 (c) is the Tafel slope diagram. It can be seen that at 10 mA cm -2 The overpotential of Ni-BTC is the largest, which is 349mV. In comparison, the performance of the bimetallic NiFe-BTC synthesized by introducing Fe has been further improved, and its overpotential has dropped to 273mV. Furthermore, the performance of NiFe-BTC-OAc and NiFe-BTC-PhCOO has been further improved, and the overpotential has dropped to 263mV and 264mV, respectively. More obviously, compared with NiFe-BTC, the overpotential in the high voltage region has dropped more significantly, further illustrating that carboxylic acids can further improve the electrocatalytic oxygen evolution performance of MOFs materials by regulating the morphology and structure of MOFs materials. The Tafel diagram intuitively shows the electrochemical kinetic behavior of various materials in the electrocatalytic process. Compared with Ni-BTC and NiFe-BTC, NiFe-BTC-OAc and NiFe-BTC-PhCOO and the Tafel slope have dropped from the original 179.4mV·dec -1 They dropped to 55mV·dec -1 and 71.4mV·dec -1 , which further illustrates that monocarboxylic acids can not only reduce the overpotential of MOFs materials, but also accelerate the kinetic behavior of the electrocatalytic oxygen evolution process.

[0057] Figure 8 CV curves of electrodes prepared using the MOF materials of Examples 1-2 and Comparative Examples 1-2 in the potential range of 0096-1.096 V, wherein: Figure 8 (a) is an electrode prepared using NiFe-BTC. Figure 8 (b) is an electrode prepared using NiFe-BTC-PhCOO. Figure 8 (c) is an electrode prepared using Ni-BTC. Figure 8 (d) is an electrode prepared using NiFe-BTC-OAc. The electrochemically active area (ESCA) of the catalyst can be calculated according to Figure 8 The double layer capacitance (C dl ) is used to measure the size of the electrochemical surface area, such as Fig. 9 shown. Fig. 9 This is a graph showing the relationship between the current density difference at 1.07V of electrodes prepared using the MOF materials of Example 1-2 and Comparative Example 1-2 and the scan rate in the non-Faraday range. It can be seen that the double layer capacitances of Ni-BTC, NiFe-BTC, NiFe-BTC-OAc and NiFe-BTC-PhCOO are similar, and only slightly increased compared to NiFe-BTC, NiFe-BTC-OAc and NiFe-BTC-PhCOO, indicating that the electrochemical active area of ​​the MOFs material did not change significantly before and after the addition of monocarboxylic acid regulation, further proving that the monocarboxylic acid regulation did not change the active area of ​​the MOFs material. Secondly, the electrocatalytic OER performance is improved by changing the local electronic structure of the active site and increasing the intrinsic activity of the active site.

[0058] Fig.10 The electrochemical impedance spectra of the electrodes prepared using the MOF materials of Examples 1-2 and Comparative Examples 1-2 show that, compared with the other three samples, the NiFe-BTC-OAc prepared in Example 1 has a smaller semicircle radius, indicating that its resistance during the electrochemical reaction is smaller, showing that it has lower charge transfer resistance and faster electrocatalytic kinetics.

Claims

1. A method for preparing a NiFe-BTC-based MOF material, characterized in that: The steps include: (1) adding nickel acetate tetrahydrate and ferrous sulfate heptahydrate into a mixed solvent consisting of DMF, anhydrous ethanol and deionized water, and dissolving them completely to obtain a mixed solution of nickel acetate and ferrous sulfate; (2) adding trimesic acid into DMF to dissolve, then adding monocarboxylate, mixing evenly, adding to the mixed solution of nickel acetate and ferrous sulfate obtained in step (1), mixing evenly, stirring and reacting at 120-180° C. to obtain a reaction product; (3) The reaction product is separated into solid and liquid, and then washed and dried to obtain a NiFe-BTC-based MOF material.

2. The method for preparing the NiFe-BTC based MOF material according to claim 1, wherein In step (1), the molar ratio of the nickel acetate tetrahydrate to the ferrous sulfate heptahydrate is 2:

1.

3. The method for preparing the NiFe-BTC based MOF material according to claim 1, wherein In step (1), in the mixed solvent, the volume ratio of DMF, anhydrous ethanol and deionized water is 1:2:

2.

4. The method for preparing the NiFe-BTC based MOF material according to claim 1, wherein In step (2), the monocarboxylate is sodium acetate or ammonium benzoate.

5. The method for preparing the NiFe-BTC based MOF material according to claim 1, characterized in that: In step (2), the molar ratio of trimesic acid to nickel acetate tetrahydrate is (0.5-1):1, and the molar ratio of the monocarboxylate to trimesic acid is (0.5-1):

1.

6. The method for preparing the NiFe-BTC based MOF material according to claim 1, characterized in that: In step (2), the reaction temperature is 150° C. and the reaction time is 6 hours.

7. The method for preparing the NiFe-BTC based MOF material according to any one of claims 1 to 6, characterized in that: In step (3), the drying temperature is 60° C. and the drying time is 12 h.

8. A NiFe-BTC based MOF material prepared by the method according to any one of claims 1 to 7.

9. Use of the NiFe-BTC-based MOF material prepared by the method according to any one of claims 1 to 7 as an electrocatalyst in hydrogen production by water electrolysis.